Perancangan Aplikasi Input Surat Berbasis VBA (Visual Basic for Application) di Kantor Sekretariat Daerah Kabupaten Gunung Mas - Nadilla Barasantika; Ade S. Permadi; Siti Arnisyah (VISA: Journal of Vision and Ideas, 2024)
Electronic archiving can be easily stored in digital storage, accessed from various locations using devices connected to the internet, and available search features that make it faster and more effective. in this study, a VBA-based letter input information system design was carried out to facilitate Regional Secretariat Office specially at the people’s welfare section in archiving incoming and outgoing letters. So that it is expected to be one of the solutions so that it can be implemented and realized by the relevant agencies. The research method used is qualitative with a case study approach. The results of the research are that the correspondence administration system no longer uses manual methods and make it easier to collect data, search and make reports on correspondence with relevant agencies.